2022
DOI: 10.1186/s12910-022-00832-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical ethics consultations: a scoping review of reported outcomes

Abstract: Background Clinical ethics consultations (CEC) can be complex interventions, involving multiple methods, stakeholders, and competing ethical values. Despite longstanding calls for rigorous evaluation in the field, progress has been limited. The Medical Research Council (MRC) proposed guidelines for evaluating the effectiveness of complex interventions. The evaluation of CEC may benefit from application of the MRC framework to advance the transparency and methodological rigor of this field. A fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…There is conflicting evidence regarding impacts of CES on quality experienced by providers, resource and cost utilization, clinical outcomes, and communication (38). Nonetheless, there is emerging evidence for alleviating provider moral distress through enhanced ethical literacy (36). Our cohort had a very high rate of moral distress identified as an ethical theme in EC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is conflicting evidence regarding impacts of CES on quality experienced by providers, resource and cost utilization, clinical outcomes, and communication (38). Nonetheless, there is emerging evidence for alleviating provider moral distress through enhanced ethical literacy (36). Our cohort had a very high rate of moral distress identified as an ethical theme in EC.…”
Section: Discussionmentioning
confidence: 99%
“…Our cohort had a very high rate of moral distress identified as an ethical theme in EC. Moral distress has been linked to poor ethical climate with adverse impacts on staff well-being, performance, retention and burnout, so targeted interventions may have multifaceted benefits (26, 35, 36). Earlier identification of simmering ethical issues and utilization EC services, may help to prevent and/or mitigate moral distress (39).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been attempts to establish core competency guidelines for ECS in the United States, most notably by the American Society for Bioethics and Humanities (ASBH), 18 though additional guidelines have been influential, such as those by the Catholic Health Association and Ascension Health, 19 and by the US Department of Veterans Affairs, 20 Another confounder in the variability of ECS roles and expectations is that there has been little adoption of these guidelines among US hospitals as hospitals continue to vary widely in ethics practice. 21 The study of ECS nationally is further limited by the lack of consensus about appropriate ECS outcome measures to research, 22,23 though notably, some positive outcomes have been reported. 24,25 What is the role of hospital ethics consultation in dementia?…”
Section: What Is the General Role Of Hospital Ethics Consultation?mentioning
confidence: 99%